Isolation, Economic Precarity, and Previous Mental Health Issues as Predictors of PTSD Status in Females Living in Fort McMurray During COVID-19 - Pazderka, Hannah; Shalaby, Reham; Eboreime, Ejemai; Mao, Wanying; Obuobi-Donkor, Gloria; Agyapong, Belinda; Oluwasina, Folajinmi; Adu, Medard Kofi; Owusu, Ernest; Sapara, Adegboyega; Agyapong, Vincent I. O. (Frontiers in Psychiatry, 2022)
Objectives: The COVID-19 pandemic represents an instance of collective trauma across the globe; as such, it is unique to our lifetimes. COVID-19 has made clear systemic disparities in terms of access to healthcare and economic precarity. Our objective was to examine the mental health repercussions of COVID-19 on adult females living in Fort McMurray, Canada in light of their unique circumstances and challenges. Method: To investigate this issue, we analysed responses gathered from an anonymous cross-section of online survey questionnaire responses gathered from females living in the Fort McMurray area (n = 159) during the COVID-19 pandemic (April 24 – June 2, 2021). This included relevant demographic, mental health history, and post-traumatic stress disorder (PTSD), as well as COVID-19 data. Chi-squared analysis was used to determine outcome relevance, and binary logistic regression was employed to generate a model of susceptibility to PTSD. Results: 159 females completed the survey. The prevalence of putative PTSD in our sample was 40.8%. A regression analysis revealed 4 variables with significant, unique contributions to PTSD. These were: a diagnosis of depression; a diagnosis of anxiety; job loss due to COVID-19; and lack of support from family and friends. Specifically, women with a previous diagnosis of either depression or anxiety were approximately 4-5 times more likely to present with PTSD symptomatology in the wake of COVID-19 (OR= 3.846; 95% CI: 1.13-13.13 for depression; OR= 5.190; 95% CI: 1.42-19.00 for anxiety). Women who reported having lost their jobs as a result of the pandemic were approximately 5 times more likely to show evidence of probable PTSD (OR= 5.182; 95% CI: 1.08-24.85). Receiving inadequate support from family and friends made the individual approximately four times as likely to develop probable PTSD (OR= 4.258; 95% CI: 1.24-14.65), while controlling for the other variables in the regression model. Conclusions: Overall, these results support our hypothesis that volatility in factors such as social support, economic stability, and mental health work together to increase the probability of women developing PTSD in response to a collective trauma such as COVID-19.